2011
DOI: 10.1083/jcb.201102051
|View full text |Cite
|
Sign up to set email alerts
|

A cell-autonomous requirement for neutral sphingomyelinase 2 in bone mineralization

Abstract: nSMase2, which cleaves sphingomyelin to generate bioactive lipids, is required for chondrocyte apoptosis and, cell autonomously, for bone mineralization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
83
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 32 publications
(54 reference statements)
3
83
0
Order By: Relevance
“…We showed that the restoration of Smpd3 expression in the osteoblasts of fro/fro; Col1a1-Smpd3 mice is sufficient to correct the bone mineralization defects. However, the cartilage abnormalities, which include an expanded zone of hypertrophic chondrocyte-like cells and poor mineralization of the cartilage matrix surrounding these cells in the growth plate, persist in this model (5). These findings suggest that SMPD3 may have distinct roles in bone and cartilage development.…”
Section: Stoffel Et Al Identified the Skeletal Abnormalities In Smpd3mentioning
confidence: 74%
See 4 more Smart Citations
“…We showed that the restoration of Smpd3 expression in the osteoblasts of fro/fro; Col1a1-Smpd3 mice is sufficient to correct the bone mineralization defects. However, the cartilage abnormalities, which include an expanded zone of hypertrophic chondrocyte-like cells and poor mineralization of the cartilage matrix surrounding these cells in the growth plate, persist in this model (5). These findings suggest that SMPD3 may have distinct roles in bone and cartilage development.…”
Section: Stoffel Et Al Identified the Skeletal Abnormalities In Smpd3mentioning
confidence: 74%
“…Relative gene expression analysis was performed as described previously (21). The primer sequences for Runx2, Sox9, Col10a1, Smpd3, Alpl, Col1a1, and Osx were the same as those published previously (5,21). The primers F2 and R2 mentioned above were used to detect third loxP site expression in the Smpd3 gene.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations